HUBUNGAN KEBIASAAN SARAPAN DAN AKTIVITAS FISIK DENGAN KONSENTRASI BELAJAR SISWA/I KELAS VIII SMPN 28 BATAM TAHUN 2023 - Bintang, Malahayati Rusli; Tjendera, Mariaman; Wulandari, Sinta Tri (Universitas Batam, 2023)
Background: Learning concentration is the ability to focus the mind on something without being influenced by the surrounding circumstances. Learning concentration is influenced by two factors, namely internal and external. Breakfast habits and physical activity are included in the internal factors of learning concentration. The purpose of this study was to determine the relationship between breakfast habits and physical activity with the concentration of learning students of grade VIII SMPN 28 Batam. Method: This type of research is quantitative with a cross-sectional approach. The population of this study was class VIII students at SMPN 28 Batam as many as 292 people. The study sample was taken from as many as 72 people with purposive techniques. Data on breakfast habits and physical activity were obtained by questionnaire and study concentration using the Stroop test. The data were analyzed using the chi–square test. Results: Breakfast habits respondents had good breakfast habits by 82.4%. The frequency of physical activity of respondents was categorized at a moderate physical activity level of 45.6%. The frequency of respondents' learning concentration obtained balanced results between good and bad concentration by 50%. The results of the chi-square test obtained p value = 0.525 for the relationship between breakfast habits with learning concentration, and the relationship between physical activity with learning concentration obtained p value = 0.084. Conclusion: There is no significant relationship between breakfast habits and physical activity of grade VIII students of SMPN 28 Batam.